Postacute care in health maintenance organizations : implications for bundling - Jacobson, Peter D.; Kahan, James P.; Noehrenberg, Peter C., 1960-; Rand eBooks (Santa Monica, CA : RAND, 1992)
Recent structural changes in health care delivery suggest that the formerly distinct managed care and fee-for-service (FFS) sectors are becoming increasingly blended. Many health care policymakers are interested in exploring whether managed care innovations can be applied to FFS providers. In this report, the authors closely examine the potential for one such blend--namely, expanding the prospective payment system (PPS) to include both hospital-based acute care and postacute care services in one bundled payment. The authors conducted a case study of selected HMOs to determine whether HMO postacute care innovations can be replicated in the FFS sector under a bundled payment system. They identified the salient HMO postacute care innovations that might be replicable, and what barriers might impede replicability. The results suggest that, at least for postacute care, aspects of the managed care system cannot easily be engrafted into the FFS sector, absent the management system and incentives embedded within managed care delivery. Because managed care and FFS represent different views of the world, there are limits to how successfully a hybrid system can be created.
"RAND/UCLA/Harvard Center for Health Care Financing Policy Research."
Includes bibliographical references (p. 53-55).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Health maintenance organizations -- United States -- Evaluation; Health maintenance organizations -- United States -- Management; Hospitals -- Prospective payment; Insurance, Health -- United States; Managed care plans (Medical care) -- United States -- Evaluation; Managed care plans (Medical care) -- United States -- Management; Medical care -- United States -- Finance; Medical policy -- United States; Electronic books